Gender Norms and the Motherhood Employment Gap - Simone Moriconi; Núria Rodríguez-Planas (Institute of Labor Economics (IZA), 2021)
Using individual-level data from the European Social Survey, we study the relevance of gender norms in accounting for the motherhood employment gap across 186 European NUTS2 regions (over 29 countries) for the 2002-2016 period. The gender norm variable is taken from a question on whether "men should have more right to a job than women when jobs are scarce" and represents the average extent of disagreement (on a scale 1 to 5) of women belonging to the "grandmothers" cohort. We address the potential endogeneity of our gender norms measure with an index of the degree of reproductive health liberalization when grandmothers were 20 years old. We also account for the endogeneity of motherhood with the level of reproductive health liberalization when mothers were 20 years old. We find a robust positive association between progressive beliefs among the grandmothers' cohort and mothers' likelihood to work while having a small child (0 to 5 years old) relative to similar women without children. No similar association is found among men. Our analysis underscores the role of gender norms and maternal employment, suggesting that non-traditional gender norms mediate on the employment gender gap mainly via motherhood.
Keywords: J16; J22; 330; gender norms; motherhood employment gap; instrumenting for motherhood